Thermal properties of porcelain reinforced polyester resin composites (Bangladesh Journal of Scientific and Industrial Research, 2017)
Porcelain reinforced polyester resin composites (PPCs) having different compositions have been prepared by compression molding. Thermal properties of PPCs were studied by means of TG-DTA and TMA. The influence of porcelain content on thermal properties of PPCs was studied in detail. Thermal conductivities of PPCs decreased from 0.00068 cal/cm sec°C to 0.00030 cal/cm sec°C by the addition of porcelain from 10 to 60%. The results of this study reveal their good thermal stabilities. The 50% degradation temperature of pure Polyester resin was 401.5°C, but that of the PPC-1, PPC-2 and PPC-4 were 406.3°C, 407.8°C, and 417.3°C respectively. The morphology of the composites was studied with scanning electron microscopy (SEM).Bangladesh J. Sci. Ind. Res. 52(2), 147-152, 2017